Empirical Studies of an Educational Tool for Project Management based on PMBOK using Problem-Based Learning - Bernardino, Maicon; Abner, Lucas; Pieva, Lucas; Araujo, Thiago; Dias, Matheus; Machado, Rodrigo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
The adopted Project Management (PM) process and management tool can determine the success or failure of a project. Academia and industry have developed many tools, techniques, and methods to assist the PM process. The Project Management Body of Knowledge (PMBOK®) aggregates a set of PM practices widely used in industry and academia. Based on the literature on the area, some gaps remain, such as the lack of tools helping the PM learning process, i.e., an issue related to the adequacy of a web-based tool in educational contexts. This study aims to introduce an educational approach based on problem-based learning and a novel educational tool covering all the knowledge areas of PMBOK®, namely Silver Bullet, that contributes to the PM process in educational contexts and supports our approach. To evaluate Silver Bullet, we conducted two empirical studies involving undergraduate students as subjects using problem-based learning in a software project manager: a quasi-experiment and a case study. We conclude that the Silver Bullet helps project managers in classroom environments by reducing the effort inherent in a PM execution process. Besides, some improvements in scoping the teaching-learning process are observed, such as activity verification, lessons learned board and log registers. Thus, we present relevant findings directing ongoing improvement.